Langerin-expressing dendritic cells in pulmonary immune-related diseases - Xuan, Shurui; Li, Yuebei; Wu, Yunhui; Adcock, Ian M.; Zeng, Xiaoning; Yao, Xin (Frontiers in Medicine, 2022)
Dendritic cells (DCs) are "frontline" immune cells dedicated to antigen presentation. They serve as an important bridge connecting innate and adaptive immunity, and express various receptors for antigen capture. DCs are divided into various subclasses according to their differential expression of cell surface receptors and different subclasses of DCs exhibit specific immunological characteristics. Exploring the common features of each sub-category has become the focus of many studies. There are certain amounts of DCs expressing langerin in airways and peripheral lungs while the precise mechanism by which langerin+ DCs drive pulmonary disease is unclear. Langerin-expressing DCs can be further subdivided into numerous subtypes based on the co-expressed receptors, but here, we identify commonalities across these subtypes that point to the major role of langerin. Better understanding is required to clarify key disease pathways and determine potential new therapeutic approaches.